2023
DOI: 10.1002/adfm.202214771
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of Segmented GeTe/(Bi,Sb)2Te3 Thermoelectric Module with Enhanced Conversion Efficiency

Abstract: GeTe and (Bi,Sb) 2 Te 3 are two representative thermoelectric (TE) materials showing maximum performance at middle and low temperature, respectively. In order to achieve higher performance over the whole temperature range, their segmented one-leg TE modules are designed and fabricated by one-step spark plasma sintering (SPS). To search for contact and connect layers, the diffusion behavior of Fe, Ni, Cu, and Ti metal layers in GeTe is studied systematically. The results show that Ti with a similar linear expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…2d . Figure 1a shows the interfacial band diagram of the boron and GeTe, showing the work functions of two materials (GeTe: ~5.09 eV 43 , boron: ~4.45 eV 44 ). The interface contact between the matrix and the boron inclusion is exactly a p-p homojunction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2d . Figure 1a shows the interfacial band diagram of the boron and GeTe, showing the work functions of two materials (GeTe: ~5.09 eV 43 , boron: ~4.45 eV 44 ). The interface contact between the matrix and the boron inclusion is exactly a p-p homojunction.…”
Section: Resultsmentioning
confidence: 99%
“…31 ). The output power density and conversion efficiency of the segmented single-leg device were simulated as a function of the current and the height ratio via the finite element method 43 . The total height of the single-leg was set as 9 mm, where the height ratio of (Bi,Sb) 2 Te 3 to GeTe was defined as x /(1− x ).…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] Due to its excellent TE performance in the low temperature region, BST is often used as the low-temperature part of segmented devices to obtain high efficiency at large temperature differences. [20][21][22][23] For example, Hu et al demonstrated an efficiency of B11% under a DT of 590 K in a segmented Bi 2 Te 3 /PbTe module. 23 Zhang et al reported a high efficiency of up to 12% in a Bi 2 Te 3 /SKD segmented module under a temperature difference of 541 K. 20 Although existing segmented devices have achieved high efficiency, they are all obtained at high hot-side temperatures and their efficiency within the temperature range of low-grade waste heat recovery is not competitive.…”
Section: Introductionmentioning
confidence: 99%
“…The foundation of thermoelectric technology is thermoelectric materials, which can realize direct and reversible energy conversion between heat and electricity. [6][7][8] As an energy conversion technology, thermoelectric conversion efficiency (Z) 9,10 is typically considered to be the most important performance indicator. The Z is dominated by the dimensionless figure of merit (zT) of thermoelectric materials, 11,12 defined as zT = S 2 sT/k, where S is the Seebeck coefficient, s is the electrical conductivity, T is the absolute temperature, and k is the total thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%